New methods of surgical treatment of rare tumours of heart - R.M. Vitovsky; V.V. Isayenko; A.O. Rusnak; B.G. Gulak; O.A. Pishchurin (Кардіохірургія та інтервенційна кардіологія)
New methods of surgical treatment of rare tumours of heart Among benign heart tumors, except most frequently observed myxomas (89.6 % саses), non-myxomatous benign tumours, including fibromas (0.4 % саses) may be diagnosed. Two cases of tumours of rare localizations, i.e. in right atrium and left ventricle, are presented. In both cases low-invasive technics using videocameras, significantly facilitating procedures inside the heart, were used. Usage of low-invasive approaches with video assistance in cardiac surgery, contrary to standard sternotomy, significantly decreases intrasurgery trauma and blood loss, as well as pain syndrome after surgery. This facilitates early rehabilitation of the patients and decreases its terms. At the same time the complete spectrum of intracardiac surgical manipulations and methods is preserved. The development of this direction in cardiac surgery is very perspective, but the individualized approach to every patient is needed.